Embedding speech pathology in an Aboriginal community-controlled playgroup: Perceptions from the community - Webb, Gwendalyn; Bird, Bella (The Australian Journal of Indigenous Education, 2023)
Colonisation in Australia has had long-term, pervasive, detrimental impacts on Indigenous Australians. When measured by national benchmarks, Indigenous children in Australia are currently at increased risk of developmental difficulties in comparison to their non-Indigenous peers. Community-led initiatives, such as playgroups, can provide safe and developmentally stimulating environments for Indigenous infants and young children, and deliver lasting benefits. These contexts also provide opportunities for collaborative approaches to develop children’s early communication skills. A participatory action research approach was applied to explore parent/carer perspectives about incorporating speech pathology into an existing community-led Aboriginal playgroup in an urban context. The speech pathology service took the form of information sharing sessions between the speech pathologist and the playgroup members. Collaborative planning and implementation of the project was followed by discussion among the participants and co-researchers about the cultural safety and helpfulness of the speech pathology service. The complexity of incorporating services delivered by non-Indigenous people in an Aboriginal community-controlled playgroup was acknowledged. The information sharing sessions were regarded as helpful and acceptable by the community. However, in the planning and implementation of the service, cultural and community needs must be considered as a precedent and priority to ensure a culturally safe and strong environment.